Brexit Beyond the UK's Borders: What It Means for Africa - Ansorg, Nadine; Haastrup, Toni (2016)
Abstract: The result of the United Kingdom’s referendum on leaving the EU, which was held on 23 June 2016, has profound geopolitical, economic, and social implications for Africa. This is all the more the case given the bilateral UK–Africa relationship and interregional Africa–EU relations. In economic terms, those African countries that rely most on trade with the UK - Nigeria, South Africa, Egypt, and Kenya - will suffer in the event of a recession in the UK. They will also feel the uncertainty that comes with renegotiating economic partnerships, which could take years. A recession in the UK would also call into question the country's ability to fulfil its aid and development commitments. Initial evidence suggests that the new government's focus will be more on strengthening trade relations than helping those most in need. African states will lose an important advocate within the EU, creating a climate of uncertainty around economic relations. In the past, the UK has advocated for the refo